An investigation into the evolution of sustainability reporting among the JSE top 10 socially-responsible companies - Memela, Melody (Research of GSB, 2018)
Corporate sustainability reporting is an important part of corporate reporting, and also an important part of creating a visibility about the sustainable agenda of corporates. Motivated by a lack of in-depth information about how this practise has evolved in South Africa; the objectives of this study are to shed more light into this evolution, as well as the quality of the content that is part of that evolution in the research period of 2002 – 2012. Segmenting the decade into through anchor points for the research, the methodology of content analysis was employed in order to read and interpret sample reports and conduct scoring across own developed evaluation criteria of six reporting categories, which was made up of a total of 62 assessment items. Reporting performance was determined, coded, summarized and aggregated where required, in order for the different levels of analysis to be carried out. The findings revealed a rising growth trend in the evolution of sustainability reporting in South Africa, with the highest growth taking place in the middle section of the research period, and significantly lower growth in the last section. This is both in terms of overall reporting as well as content coverage of the different reporting categories included in the research. The Social Performance category is the most reported on category through the decade. The highest percentage increase is found to be in the Context & Commitment and Quality of Management reporting categories through the decade. The industrial sector is the top performer and Telecoms the bottom performer in terms of overall reporting performance for the decade. Sustainability reporting in South Africa seems to have experienced an overall growth trend similar to the global trend. However the evolution of that growth has highlighted certain country specific nuances through the reporting period.